Peran Kemenag Depok dalam Mengembangkan Kurikulum di MI Terpadu Fatahillah - Tulvonidasari, Latifa; Aisyatunnadiya, Siti (Indo-MathEdu Intellectuals Journal, 2026)
The ideal curriculum development in Madrasah Ibtidaiyah (MI) should be able to create a curriculum that is dynamic, contextual, and adaptive to the development of the times. The purpose of this research is to analyze the role of Depok ministry in developing the curriculum in MI Fatahillah. This research uses descriptive qualitative, case study. From the results of the discussion of this research, it shows that the development of the curriculum in Madrasah Ibtidaiyah (MI) Integrated Fatahillah includes the strategic efforts of the Head of the Madrasah Section, in the midst of various challenges. The Section Head emphasizes an adaptive and inclusive approach by involving all stakeholders, such as teachers, students, and parents, to ensure the relevance of the curriculum. The application of innovative learning methods, including project-based learning and technology, aims to improve the quality of education. Implementation includes ongoing training for teachers and adequate infrastructure support. Collaboration with educational institutions is also expected to facilitate the exchange of knowledge. The new curriculum development concept emphasizes the integration of character values, the use of technology, and a holistic approach, not only for academic achievement, but also for shaping the personality of students. Overall, the effort is committed to creating a positive and adaptive learning environment, making students intelligent individuals with good character.